Child-friendly justice - Turhan, Ozan (Pravnik, 2015)
Even though the European Union set of as an economic integration project, through a more holistic approach to EU law the EU legislator and to a greater extent also the European Court of Justice gradually adapted the protection of EU law related to the free movement to heed children. With regard to the free movement of persons first only as family members of EU workers, then as individual bearers of rights to education and residence as relatives of (former) EU workers, and lately as EU citizens that are principally endowed with the same rights as EU citizens of age.
Keywords: child; človekove pravice; European Union; Evropska unija; human rights; otroci; sodna praksa